News Startups as Agents of Innovation: For-profit digital news startup manifestos as metajournalistic discourse. Issue 5 (3rd July 2016) - Carlson, Matt; Usher, Nikki
Abstract : For-profit digital news startups backed by large investors, venture capital, and technology entrepreneurs have taken on an increasingly significant role in the journalism industry. This article examines 10 startups by focusing on the manifestos these new organizations offer when they introduce themselves to the public. These manifestos are an example of metajournalistic discourse, or interpretive discourse about journalism, that publicly define how journalism is changing—or is not. In identifying and touting the superiority of their technological innovations, the manifestos simultaneously affirm and critique existing journalistic practices while rethinking longstanding boundaries between journalism and technology.